Secure vehicle to vehicle voice chat based MQTT and CoAP internet of things protocol - Noor A. Hussein; Mohamed Ibrahim. Shujaa (Institute of Advanced Engineering and Science, 2020)
The congestion of road traffic is one of the most problems facing the ambulance transportation to provide fast healthcare service for patient. In this work, ambulance tracking with messages transfer system has been designed and implemented such that a central monitoring and tracking unit can observe ambulance using MQTT IoT protocol. Where each vehicle is occupied with an intelligent embedded system (Raspberry Pi) unit. When an ambulance is being in the road, it will communicate with other vehicle or road traffic by means of CoAP IoT protocol as a direct device to device communication. The proposed system has been designed such that driver use voice chat and the system are completely hand free. The voice message is being transfer into text by using speech recognition based Google API library, and then the received text message is converted again to speech by using text to speech algorithm. An encryption–decryption process-based stream cipher has been used. The message between IoT nodes has been encrypted using One Time Pad (OTP) and DNA computing. Furthermore, the required key sequence was generated using a linear feedback shift register (LFSR) as a pseudo number key generator. This key sequence was combined to generate a unique key for each message.